Genetic polymorphisms of EGF 5'-UTR and NAT2 857G/A associated with glioma in a case control study of Malaysian patients - Muthusamy, K.A.; Lian, L.H.; Vairavan, N.; Chua, K.H.; Waran, V. (2012)
Studies of genetic mutations that have been used in predicting glioma prognosis have revealed a complex relationship between clinical and genetic factors. Epidermal growth factor (EGF) and the NAT2 gene play a central role in carcinogenesis. An adenine (A) to guanine (G) single nucleotide polymorphism at position 61 in the 5'-untranslated region (5'-UTR) of the EGF gene has been found to be associated with levels of EGF production, and the mutations in the NAT2 gene have been postulated as a risk factor for cancer. We investigated EGF and the NAT2 gene in 13 glioma tissue samples and 12 normal controls. In the EGF 5'-UTR 61G polymorphism, the heterozygote GA was the most common genotype in the glioma patients. In the NAT2 polymorphism at nucleotide position 857G/A, the G allele and the GG genotype were the most prevalent forms in both the glioma and normal samples. We did not find any homozygous AA genotypes in the glioma patients. Based on this preliminary evidence, the EGF 5'-UTR at position 61 and the NAT2 SNP at position 857 polymorphisms are associated with increased risk for glioma.